Preparation method of loose nanofiltration membrane, nanofiltration membrane and application

Hydrophilic carbon nitride solution was prepared by sintering and dialysis, and combined with polyacid chloride monomers in the interfacial polymerization reaction to form a loose nanofiltration membrane, which solved the unsatisfactory efficiency of existing nanofiltration membranes in salt and dye separation applications. The problem of high efficiency separation and high permeability flux are achieved.

CN119455685AActive Publication Date: 2025-02-18TSINGHUA UNIVERSITY
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411603204.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-18
Estimated Expiration
2044-11-11

AI Technical Summary

Technical Problem

现有纳滤膜在盐和染料的分离应用中存在效率不理想的问题,且制备工艺复杂,成本高,难以满足实际应用需求。

Method used

Carbon nitride is prepared by sintering the nitrogen-containing precursor and alkali, and then dialyzed to obtain a hydrophilic carbon nitride solution. The solution is used to infiltrate the ultrafiltration support base membrane and is then used to connect with polyacrylic acid chloride monomers in the interfacial polymerization reaction. Combined to form a loose nanofiltration membrane.

Benefits of technology

It achieves efficient separation of various dyes and salt ions in water, and increases the permeability flux by about 4 times, meeting the separation effect and flux requirements for practical applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119455685A_ABST
    Figure CN119455685A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of water treatment membrane materials, particularly discloses a preparation method of a loose nanofiltration membrane, and further discloses the prepared loose nanofiltration membrane and application thereof. According to the preparation method disclosed by the invention, a high-hydrophilicity interface structure and carbon nitride with a large number of cyano and amino structures are used as water-phase monomers and are subjected to polymerization reaction with multi-element acyl chloride monomers in an oil phase on an interface, and the interfacial polymerization process is regulated and controlled through a carbon nitride functional layer; and the loose nanofiltration membrane with high separation selectivity and high permeability to dye / salt wastewater can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of water treatment membrane materials, in particular to a method for preparing a loose nanofiltration membrane, and also to the prepared nanofiltration membrane and applications thereof. Background Art

[0002] With the rapid development of the textile printing and dyeing industry, the discharge of production wastewater has increased sharply year by year. Since inorganic salts such as sodium chloride (about 6.0wt%) and sodium sulfate (about 5.6wt%) are often introduced in the process of fabric dyeing to promote the absorption of dyes by fibers, the coexistence of dyes and salt ions in the discharged wastewater has become a common feature of such wastewater. The effective separation of organic dye / inorganic salt ion mixtures is of great significance for the efficient treatment of textile printing and dyeing wastewater and the effective recovery of valuable substances in water. Nanofiltration membranes with loose structures can selectively pass through inorganic salts while intercepting dye molecules, thereby achieving effective separation of these two types of substances. Therefore, they have broad application prospects in the treatment of printing and dyeing wastewater.

[0003] The preparation of existing nanofiltration membranes usually adopts a method based on the polymerization reaction of polyamine monomers in the water phase and polyacyl chloride monomers in the oil phase at the interface, mainly based on the polymerization of trimesoyl chloride (TMC) and piperazine (PIP) on the surface of the base membrane to form an ultra-thin polyamide functional layer. Due to the fast reaction rate between the polyamine monomers and the polyacyl chloride monomers, it is difficult to achieve precise control of the growth process of the polyamide functional layer, resulting in the formation of a thick, dense polyamide functional layer with a wide pore size distribution and low water flux. The efficiency is not ideal in the separation of salts and dyes.

[0004] At present, the research on loose nanofiltration membranes for the separation of dyes and salts is still in its infancy, facing problems such as high raw material costs, complex preparation processes, and separation effects that cannot meet actual application needs. There is an urgent need to develop a new loose nanofiltration membrane.

[0005] Based on the above problems, the present invention aims to develop a method for preparing a loose nanofiltration membrane to obtain a loose nanofiltration membrane with excellent performance. Summary of the invention

[0006] The main technical problem solved by the present invention is to provide a method for preparing a loose nanofiltration membrane, and the prepared loose nanofiltration membrane and application thereof.

[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing a loose nanofiltration membrane, comprising the following steps:

[0008] S1: mixing a nitrogen-containing precursor and an alkali and sintering the mixture to obtain carbon nitride, and then grinding the mixture to obtain exfoliated nanosheet carbon nitride;

[0009] S2: dialyzing the exfoliated nanosheet carbon nitride in water to prepare a hydrophilic carbon nitride solution;

[0010] S3: The ultrafiltration support bottom membrane is treated by infiltration with the hydrophilic carbon nitride solution;

[0011] S4: placing the ultrafiltration support bottom membrane treated in step S3 into a solution containing an organic phase monomer to perform an interfacial polymerization reaction to obtain a loose nanofiltration membrane preform containing a polyamide separation layer;

[0012] S5: heat-treating the loose nanofiltration membrane preform to obtain the loose nanofiltration membrane.

[0013] As an embodiment of the present invention, the nitrogen-containing precursor is selected from at least one of cyanamide, dicyandiamide, melamine, urea and thiourea.

[0014] As an embodiment of the present invention, the alkali is selected from at least one of sodium hydroxide, potassium hydroxide and calcium hydroxide.

[0015] As a specific embodiment of the present invention, the alkali is a mixture of sodium hydroxide and potassium hydroxide.

[0016] As an embodiment of the present invention, the nitrogen-containing precursor and the base are mixed in a mass ratio of (1.8-2.0):1.

[0017] As an embodiment of the present invention, the sintering temperature is 300-350° C., and the sintering time is 1-3 hours.

[0018] Preferably, the sintering treatment is carried out in a muffle furnace, the temperature is raised to 300-350° C. at a heating rate of 4-6° C. / min, and the high-temperature sintering is carried out for 1-3 hours.

[0019] As an embodiment of the present invention, the concentration of carbon nitride in the hydrophilic carbon nitride solution is 1.0 to 3.0 mg / mL.

[0020] As an embodiment of the present invention, the dialysis treatment uses a 3500DA dialysis bag and the dialysis lasts for 12 to 48 hours.

[0021] As an embodiment of the present invention, the ultrafiltration support bottom membrane is a polycarbonate filter membrane, a polytetrafluoroethylene filter membrane, a polyethersulfone filter membrane, a polysulfone filter membrane or a polypropylene filter membrane.

[0022] As an embodiment of the present invention, the time of the infiltration treatment is 5 to 30 minutes.

[0023] As an embodiment of the present invention, the concentration of the organic phase monomer in the solution containing the organic phase monomer is 1 to 3 mg / mL.

[0024] As an embodiment of the present invention, the organic phase monomer is at least one selected from isophthaloyl chloride, terephthaloyl chloride, 1,3,5-trimesoyl chloride, pyromellitoyl chloride, cycloalkane polyacyl chloride, and polysulfonyl chloride.

[0025] Preferably, the organic phase monomer is 1,3,5-trimethylbenzenecarboxylic acid chloride.

[0026] As an embodiment of the present invention, the solution containing organic phase monomers is an organic solvent solution of organic phase monomers, and the organic solvent is selected from at least one of n-hexane, n-octane, n-heptane, dichloromethane, chloroform, carbon tetrachloride, benzene, toluene, xylene, pentane, and cyclohexane.

[0027] As an embodiment of the present invention, the reaction temperature of the interfacial polymerization reaction is 20-30° C., the reaction time is 2-10 min, and the reaction environment humidity is 45-70%.

[0028] As an embodiment of the present invention, the heat treatment conditions are: heating at 40-70° C. for 10-60 min.

[0029] The present invention also provides a loose nanofiltration membrane, which is obtained by adopting the preparation method of the present invention.

[0030] The present invention further provides an application of a loose nanofiltration membrane, preferably an application in water treatment, and further preferably an application in printing and dyeing wastewater treatment.

[0031] The invention provides a method for preparing a loose nanofiltration membrane. First, carbon nitride is prepared, and then it is ground to prepare exfoliated nanosheet carbon nitride. The exfoliated nanosheet carbon nitride is then dialyzed in water to prepare a hydrophilic carbon nitride solution. An ultrafiltration support base membrane is firstly treated by infiltration with the hydrophilic carbon nitride solution, and then placed in a solution containing an organic phase monomer to carry out an interfacial polymerization reaction. The hydrophilic carbon nitride monomer in the hydrophilic carbon nitride solution has a highly hydrophilic interfacial structure and a large number of cyano and amino structures, and an organic solution containing a polyacyl chloride monomer is used to carry out an interfacial polymerization reaction, so that the rate of the polymerization reaction can be effectively regulated to obtain a loose nanofiltration membrane.

[0032] The preparation method of the present invention uses a highly hydrophilic interface structure and carbon nitride with a large number of cyano and amino structures as water phase monomers, and a polyacyl chloride monomer in an oil phase undergoes polymerization reaction at the interface, and the interface polymerization process is regulated by a carbon nitride functional layer, so as to obtain a loose nanofiltration membrane with high separation selectivity and high permeability for dye / salt wastewater. The loose nanofiltration membrane obtained by the method of the present invention can effectively separate a variety of dyes and salt ions in water under the premise of increasing the permeation flux by about 4 times. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1is a transmission electron microscope photograph of carbon nitride in the carbon nitride solution obtained in step (2) of Example 1 of the present invention;

[0034] Figure 2 This is a scanning electron microscope image of a separation and selection layer with a wrinkled morphology formed by polymerization of hydrophilic carbon nitride in a loose nanofiltration membrane prepared in Example 3 of the present invention;

[0035] Figure 3 It is a graph showing the pure water flux test results of the nanofiltration membranes prepared in Examples 1-5 of the present invention and Comparative Example 1;

[0036] Figure 4 It is a graph showing the rejection rate test results of the nanofiltration membranes prepared in Examples 1-5 of the present invention and Comparative Example 1;

[0037] Figure 5 It is a diagram showing the results of solution flux detection of different inorganic salt aqueous solutions by the nanofiltration membranes prepared in Example 3 of the present invention and Comparative Example 1;

[0038] Figure 6 It is a test result diagram of the rejection rate of the nanofiltration membranes prepared in Example 3 of the present invention and Comparative Example 1 for different inorganic salt aqueous solutions;

[0039] Figure 7 It is a diagram showing the solution flux test results of the nanofiltration membranes prepared in Example 3 of the present invention and Comparative Example 1 for different dye aqueous solutions;

[0040] Figure 8 It is a graph showing the results of the interception rate test of different dye aqueous solutions by the nanofiltration membranes prepared in Example 3 of the present invention and Comparative Example 1;

[0041] Fig. 9 It is a comparison diagram of the water contact angles of the nanofiltration membranes prepared in Examples 1 to 5 of the present invention and Comparative Example 1;

[0042] Fig.10 It is a comparison chart of the Zeta potential of the nanofiltration membranes prepared in Example 3 of the present invention and Comparative Example 1. DETAILED DESCRIPTION

[0043] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.

[0044] In the following examples and comparative examples, unless otherwise specified, the drugs used are all commercially available products.

[0045] Example 1

[0046] This embodiment provides a loose nanofiltration membrane, which is prepared by the following steps:

[0047] (1) 6 g of melamine, 0.8 g of sodium hydroxide, and 2.24 g of potassium hydroxide were fully mixed and ground in a mortar, and the obtained mixture was placed in a muffle furnace and heated from room temperature to 330° C. at a heating rate of 5° C. / min and maintained for 2 h for sintering to obtain carbon nitride, and after cooling to room temperature, the mixture was fully ground into powder to obtain exfoliated nanosheet carbon nitride;

[0048] (2) 1.0 g of exfoliated nanosheet carbon nitride powder was dissolved in 100 ml of ultrapure water and stirred thoroughly to dissolve. The supernatant was then divided into a 3500DA dialysis bag and dialyzed for 48 h to obtain a uniformly dispersed water-soluble carbon nitride solution, i.e., a hydrophilic carbon nitride solution. The concentration of the solution was characterized by ultraviolet absorbance test. The concentration of the carbon nitride solution was 1.0 mg / mL. The transmission electron microscope photo of carbon nitride in the carbon nitride solution is shown in Figure 1 , the carbon nitride solution can remain stable for several months without precipitation;

[0049] (3) Using a polyethersulfone filter membrane as an ultrafiltration support membrane, and using the hydrophilic carbon nitride solution prepared in step (2) as an aqueous phase monomer, 5 ml of the hydrophilic carbon nitride solution was dripped onto the surface of the ultrafiltration support membrane for aqueous phase infiltration, and the infiltration treatment lasted for 5 minutes, after which the liquid on the surface of the ultrafiltration support membrane was removed;

[0050] (4) The ultrafiltration support base membrane after the water phase infiltration treatment is then placed in a 2 mg / mL 1,3,5-benzene trimesoyl chloride n-hexane solution to perform an interfacial polymerization reaction. The reaction temperature is 25° C., the reaction environment humidity is 60%, and the reaction lasts for 2 minutes. After that, the ultrafiltration support base membrane after the interfacial polymerization reaction is placed in the n-hexane solution and soaked for 10 seconds to remove the residual acyl chloride monomer on the surface, thereby obtaining a loose nanofiltration membrane preform;

[0051] (5) The loose nanofiltration membrane preform obtained in step (4) is heat-treated in an oven at 60° C. for 10 min to obtain a fully polymerized loose nanofiltration membrane.

[0052] Example 2

[0053] This embodiment provides a loose nanofiltration membrane, which is prepared by the following steps:

[0054] (1) 6 g of melamine, 0.8 g of sodium hydroxide, and 2.24 g of potassium hydroxide were fully mixed and ground in a mortar, and the obtained mixture was placed in a muffle furnace and heated from room temperature to 330° C. at a heating rate of 5° C. / min and maintained for 2 h for sintering to obtain carbon nitride, and after cooling to room temperature, the mixture was fully ground into powder to obtain exfoliated nanosheet carbon nitride;

[0055] (2) 1.5 g of exfoliated nanosheet carbon nitride powder was dissolved in 100 ml of ultrapure water, and the mixture was fully stirred and dissolved. The supernatant was then divided into a 3500DA dialysis bag and dialyzed for 48 h to obtain a uniformly dispersed water-soluble carbon nitride solution, i.e., a hydrophilic carbon nitride solution. The concentration of the solution was characterized by ultraviolet absorbance test, and the concentration of the carbon nitride solution was 1.5 mg / mL.

[0056] (3) Using a polyethersulfone filter membrane as an ultrafiltration support membrane, and using the hydrophilic carbon nitride solution prepared in step (2) as an aqueous phase monomer, 5 ml of the hydrophilic carbon nitride solution was dripped onto the surface of the ultrafiltration support membrane for aqueous phase infiltration, and the infiltration treatment was performed for 5 minutes, after which the liquid on the surface of the ultrafiltration support membrane was removed;

[0057] (4) The ultrafiltration support base membrane after the water phase infiltration treatment is then placed in a 2 mg / mL 1,3,5-benzene trimesoyl chloride n-hexane solution to perform an interfacial polymerization reaction. The reaction temperature is 25° C., the reaction environment humidity is 60%, and the reaction lasts for 2 minutes. After that, the ultrafiltration support base membrane after the interfacial polymerization reaction is placed in the n-hexane solution and soaked for 10 seconds to remove the residual acyl chloride monomer on the surface, thereby obtaining a loose nanofiltration membrane preform;

[0058] (5) The loose nanofiltration membrane preform obtained in step (4) is heat-treated in an oven at 60° C. for 10 min to obtain a fully polymerized loose nanofiltration membrane.

[0059] Example 3

[0060] This embodiment provides a loose nanofiltration membrane, which is prepared by the following steps:

[0061] (1) 6 g of melamine, 0.8 g of sodium hydroxide, and 2.24 g of potassium hydroxide were fully mixed and ground in a mortar, and the obtained mixture was placed in a muffle furnace and heated from room temperature to 330° C. at a heating rate of 5° C. / min and maintained for 2 h for sintering to obtain carbon nitride, and after cooling to room temperature, the mixture was fully ground into powder to obtain exfoliated nanosheet carbon nitride;

[0062] (2) 2.0 g of exfoliated nanosheet carbon nitride powder was dissolved in 100 ml of ultrapure water, and the mixture was fully stirred and dissolved. The supernatant was then divided into a 3500DA dialysis bag and dialyzed for 48 h to obtain a uniformly dispersed water-soluble carbon nitride solution, i.e., a hydrophilic carbon nitride solution. The concentration of the solution was characterized by ultraviolet absorbance test, and the concentration of the carbon nitride solution was 2.0 mg / mL.

[0063] (3) Using a polyethersulfone filter membrane as an ultrafiltration support membrane, and using the hydrophilic carbon nitride solution prepared in step (2) as an aqueous phase monomer, 5 ml of the hydrophilic carbon nitride solution was dripped onto the surface of the ultrafiltration support membrane for aqueous phase infiltration, and the infiltration treatment was performed for 5 minutes, after which the liquid on the surface of the ultrafiltration support membrane was removed;

[0064] (4) The ultrafiltration support base membrane after the water phase infiltration treatment is then placed in a 2 mg / mL 1,3,5-benzene trimesoyl chloride n-hexane solution to perform an interfacial polymerization reaction. The reaction temperature is 25° C., the reaction environment humidity is 60%, and the reaction lasts for 2 minutes. After that, the ultrafiltration support base membrane after the interfacial polymerization reaction is placed in the n-hexane solution and soaked for 10 seconds to remove the residual acyl chloride monomer on the surface, thereby obtaining a loose nanofiltration membrane preform;

[0065] (5) The loose nanofiltration membrane preform obtained in step (4) was heat treated in an oven at 60° C. for 10 min to obtain a fully polymerized loose nanofiltration membrane. The scanning electron microscopy image of the wrinkled separation selection layer formed by the polymerization of hydrophilic carbon nitride in the loose nanofiltration membrane is shown in FIG. Figure 2 , it can be seen that the hydrophilic carbon nitride prepared membrane has a smooth and wrinkled separation layer surface.

[0066] Example 4

[0067] This embodiment provides a loose nanofiltration membrane, which is prepared by the following steps:

[0068] (1) 6 g of melamine, 0.8 g of sodium hydroxide, and 2.24 g of potassium hydroxide were fully mixed and ground in a mortar, and the obtained mixture was placed in a muffle furnace and heated from room temperature to 330° C. at a heating rate of 5° C. / min and maintained for 2 h for sintering to obtain carbon nitride, and after cooling to room temperature, the mixture was fully ground into powder to obtain exfoliated nanosheet carbon nitride;

[0069] (2) 2.5 g of exfoliated nanosheet carbon nitride powder was dissolved in 100 ml of ultrapure water, and the mixture was fully stirred and dissolved. The supernatant was then divided into a 3500DA dialysis bag and dialyzed for 48 h to obtain a uniformly dispersed water-soluble carbon nitride solution, i.e., a hydrophilic carbon nitride solution. The concentration of the solution was characterized by ultraviolet absorbance test, and the concentration of the carbon nitride solution was 2.5 mg / mL.

[0070] (3) Using a polyethersulfone filter membrane as an ultrafiltration support membrane, and using the hydrophilic carbon nitride solution prepared in step (2) as an aqueous phase monomer, 5 ml of the hydrophilic carbon nitride solution was dripped onto the surface of the ultrafiltration support membrane for aqueous phase infiltration, and the infiltration treatment was performed for 5 minutes, after which the liquid on the surface of the ultrafiltration support membrane was removed;

[0071] (4) The ultrafiltration support base membrane after the water phase infiltration treatment is then placed in a 2 mg / mL 1,3,5-benzene trimesoyl chloride n-hexane solution to perform an interfacial polymerization reaction. The reaction temperature is 25° C., the reaction environment humidity is 60%, and the reaction lasts for 2 minutes. After that, the ultrafiltration support base membrane after the interfacial polymerization reaction is placed in the n-hexane solution and soaked for 10 seconds to remove the residual acyl chloride monomer on the surface, thereby obtaining a loose nanofiltration membrane preform;

[0072] (5) The loose nanofiltration membrane preform obtained in step (4) is heat-treated in an oven at 60° C. for 10 min to obtain a fully polymerized loose nanofiltration membrane.

[0073] Example 5

[0074] This embodiment provides a loose nanofiltration membrane, which is prepared by the following steps:

[0075] (1) 6 g of melamine, 0.8 g of sodium hydroxide, and 2.24 g of potassium hydroxide were fully mixed and ground in a mortar, and the obtained mixture was placed in a muffle furnace and heated from room temperature to 330° C. at a heating rate of 5° C. / min and maintained for 2 h for sintering to obtain carbon nitride, and after cooling to room temperature, the mixture was fully ground into powder to obtain exfoliated nanosheet carbon nitride;

[0076] (2) 3.0 g of exfoliated nanosheet carbon nitride powder was dissolved in 100 ml of ultrapure water, and the mixture was fully stirred and dissolved. The supernatant was then divided into a 3500DA dialysis bag and dialyzed for 48 h to obtain a uniformly dispersed water-soluble carbon nitride solution, i.e., a hydrophilic carbon nitride solution. The concentration of the solution was characterized by ultraviolet absorbance test, and the concentration of the carbon nitride solution was 3.0 mg / mL;

[0077] (3) Using a polyethersulfone filter membrane as an ultrafiltration support membrane, and using the hydrophilic carbon nitride solution prepared in step (2) as an aqueous phase monomer, 5 ml of the hydrophilic carbon nitride solution was dripped onto the surface of the ultrafiltration support membrane for aqueous phase infiltration, and the infiltration treatment was performed for 5 minutes, after which the liquid on the surface of the ultrafiltration support membrane was removed;

[0078] (4) The ultrafiltration support base membrane after the water phase infiltration treatment is then placed in a 2 mg / mL 1,3,5-benzene trimesoyl chloride n-hexane solution to perform an interfacial polymerization reaction. The reaction temperature is 25° C., the reaction environment humidity is 60%, and the reaction lasts for 2 minutes. After that, the ultrafiltration support base membrane after the interfacial polymerization reaction is placed in the n-hexane solution and soaked for 10 seconds to remove the residual acyl chloride monomer on the surface, thereby obtaining a loose nanofiltration membrane preform;

[0079] (5) The loose nanofiltration membrane preform obtained in step (4) is heat-treated in an oven at 60° C. for 10 min to obtain a fully polymerized loose nanofiltration membrane.

[0080] Comparative Example 1

[0081] This comparative example provides a nanofiltration membrane, and the specific preparation steps are as follows:

[0082] Step 1: Take piperazine as the aqueous phase monomer and 1,3,5-trimethylbenzenecarboxylic acid chloride as the organic phase monomer, dissolve them in water and n-hexane respectively, and prepare a piperazine aqueous solution with a concentration of 4.0 mg / mL and a 1,3,5-trimethylbenzenecarboxylic acid chloride organic solution with a concentration of 2 mg / mL, and set aside;

[0083] Step 2: Using a polyethersulfone filter membrane as an ultrafiltration support bottom membrane, dripping 5 ml of a piperazine aqueous solution on the surface of the ultrafiltration support bottom membrane, performing an aqueous phase infiltration treatment, and infiltrating the treatment for 5 minutes, after which the liquid on the surface of the ultrafiltration support bottom membrane is removed;

[0084] Step 3: immersing the ultrafiltration support bottom membrane after the water phase infiltration treatment in a 1,3,5-benzene trimesoyl chloride organic solution for interfacial polymerization reaction, the reaction temperature is 25° C., the reaction environment humidity is 60%, and the reaction lasts for 2 minutes. After that, the ultrafiltration support bottom membrane after the interfacial polymerization reaction is immersed in a n-hexane solution for 10 seconds to remove the residual acyl chloride monomer on the surface, thereby obtaining a nanofiltration membrane preform;

[0085] Step 4: Heat-treat the nanofiltration membrane preform in an oven at 60° C. for 10 min to obtain a fully polymerized nanofiltration membrane.

[0086] The performance of the nanofiltration membranes prepared in the above embodiments and comparative examples was tested as follows.

[0087] (1) The nanofiltration membranes prepared in Examples 1-5 and Comparative Example 1 were respectively applied to deionized water solutions to test their performance.

[0088] The test process is as follows: 2L deionized water solution is used as the test liquid, and the separation performance of the nanofiltration membrane is tested at 4 bar by cross-flow filtration. The test liquid temperature is 25°C. After pre-pressurization at 4 bar for 30 minutes, the produced water is collected for 30 minutes, and the pure water flux of the nanofiltration membrane is calculated based on the volume of the output water.

[0089] The pure water flux test results of the nanofiltration membranes prepared in Examples 1-5 and Comparative Example 1 are shown in FIG. Figure 3 .from Figure 3 It can be seen that the pure water flux of the nanofiltration membrane prepared in Comparative Example 1 is only 10Lm-2h-1bar-1, while the pure water flux of the loose nanofiltration membrane provided by the embodiment of the present invention can reach 3-8 times that of the nanofiltration membrane prepared in Comparative Example 1.

[0090] (2) The nanofiltration membranes prepared in Examples 1-5 and Comparative Example 1 were respectively applied to a mixed aqueous solution of sodium chloride and methyl blue to test their performance.

[0091] The test process is: prepare a mixed solution containing 1000ppm sodium chloride and 200ppm methyl blue as the dye / salt mixed test solution, use cross-flow filtration to test the separation performance of the nanofiltration membrane at 4bar, the test solution temperature is 25℃, collect the produced water for 30 minutes after pre-pressurization at 4bar, calculate the retention rate of the nanofiltration membrane for salt ions based on the conductivity values ​​of the produced water and the influent water, and calculate the retention rate of the nanofiltration membrane for the dye based on the absorbance values ​​of the produced water and the influent water.

[0092] The rejection rate test results of the nanofiltration membranes prepared in Examples 1-5 and Comparative Example 1 are shown in FIG. Figure 4 .from Figure 4 It can be seen that, taking the nanofiltration membrane prepared in Example 3 as an example, it can intercept nearly 100% of methyl blue and pass nearly 90% of sodium chloride. The nanofiltration membrane of Comparative Example 1 can pass 70% of salt ions on the basis of intercepting nearly 100% of methyl blue. This shows that the loose nanofiltration membrane prepared in Example 3 of the present invention can better separate dye molecules and salt ions.

[0093] (3) The nanofiltration membranes prepared in Example 3 and Comparative Example 1 were respectively applied to different inorganic salt aqueous solutions to test their performance.

[0094] The retention rate test process is as follows: prepare aqueous solutions of sodium chloride, magnesium chloride, sodium sulfate, and magnesium sulfate, each with a concentration of 1000ppm, as test solutions; use cross-flow filtration to test the separation performance of the nanofiltration membrane at 4bar, the test liquid temperature is 25°C, and after pre-pressurization at 4bar for 30 minutes, collect the produced water for 30 minutes, and calculate the retention rate of the nanofiltration membrane for salt ions based on the conductivity values ​​of the produced water and the influent water.

[0095] The solution flux test process is as follows: prepare aqueous solutions of sodium chloride, magnesium chloride, sodium sulfate, and magnesium sulfate, each with a concentration of 1000ppm, as test solutions; use cross-flow filtration to test the separation performance of the nanofiltration membrane at 4bar, the test liquid temperature is 25°C, and after pre-pressurization at 4bar for 30 minutes, collect the produced water for 30 minutes, and calculate the solution flux of the nanofiltration membrane based on the volume of the effluent.

[0096] The results of the solution flux test of the nanofiltration membranes prepared in Example 3 and Comparative Example 1 for different inorganic salt aqueous solutions are shown in FIG. Figure 5 The interception rate test results of different inorganic salt aqueous solutions are shown in the figure Figure 6 .

[0097] from Figure 5 and Figure 6 It can be seen that the flux of the nanofiltration membrane prepared in Example 3 for sodium chloride solution is 40Lm-2h-1bar-1, and the rejection rate is 11%; the flux of the nanofiltration membrane prepared in Comparative Example 1 for sodium chloride solution is 10Lm-2h-1bar-1, and the rejection rate is 305. The flux of the nanofiltration membrane prepared in Example 3 for sodium sulfate solution is 36Lm-2h-1bar-1, and the rejection rate is 32%. The flux of the nanofiltration membrane prepared in Comparative Example 1 for sodium sulfate solution is 9Lm-2h-1bar-1, and the rejection rate is 98%. This shows that the loose nanofiltration membrane prepared in Example 3 has good permeability to salt ions.

[0098] (4) The nanofiltration membranes prepared in Example 3 and Comparative Example 1 were respectively applied to different dye aqueous solutions to test their performance.

[0099] The retention rate test process is as follows: prepare aqueous solutions of sunset yellow, rhodamine B, Congo red, brilliant green SF and methyl blue, each with a concentration of 100 ppm, as test solutions; use cross-flow filtration to test the separation performance of the nanofiltration membrane at 4 bar, the test liquid temperature is 25°C, and after pre-pressurization at 4 bar for 30 minutes, collect the produced water for 30 minutes, and calculate the retention rate of the nanofiltration membrane for the dye based on the absorbance values ​​of the produced water and the influent water.

[0100] The solution flux test process is as follows: prepare aqueous solutions of sunset yellow, rhodamine B, Congo red, brilliant green SF and methyl blue, each with a concentration of 100 ppm, as test solutions; use cross-flow filtration to test the separation performance of the nanofiltration membrane at 4 bar, the test liquid temperature is 25°C, and after pre-pressurization at 4 bar for 30 minutes, collect the produced water for 30 minutes, and calculate the solution flux of the nanofiltration membrane based on the volume of the effluent.

[0101] The results of the solution flux test of the nanofiltration membranes prepared in Example 3 and Comparative Example 1 for different dye aqueous solutions are shown in FIG. Figure 7 The interception rate test results of different dye aqueous solutions are shown in the figure Figure 8 .

[0102] from Figure 7 and Figure 8 It can be seen that the solution flux of methyl blue obtained by the nanofiltration membrane prepared in Example 3 of the present invention is 32Lm-2h-1bar-1, and the retention rate is 99%. The solution flux of methyl blue obtained by the nanofiltration membrane prepared in Comparative Example 1 is 8Lm-2h-1bar-1, and the retention rate is 99%. This shows that the loose nanofiltration membrane prepared in Example 3 has good retention performance for dyes and can maintain a high flux.

[0103] (5) The surface contact angles of the nanofiltration membranes prepared in Examples 1-5 and Comparative Example 1 were measured using an OCA25 video contact angle meter produced by Dataphysics of Germany.

[0104] The test process is as follows: ultrapure water is used as the test liquid; the nanofiltration membrane is placed on the sample table of the instrument to ensure that the sample is placed flat. A 1μL water droplet is suspended at the end of the needle, the sample table is raised to make the surface of the nanofiltration membrane contact the suspended water droplet, and then the nanofiltration membrane is removed to complete the transfer of the water droplet. When the water droplet reaches equilibrium on the surface of the nanofiltration membrane, the contact angle between them is measured by the principle of optical appearance projection. The test environment temperature condition is 25℃.

[0105] Fig. 9 The water contact angle comparison diagram of the nanofiltration membranes prepared in Examples 1 to 5 and Comparative Example 1 is shown in FIG. Fig. 9It shows that the nanofiltration membranes provided in Examples 1 to 5 of the present invention have strong hydrophilicity, which is better than the nanofiltration membrane provided in Comparative Example 1.

[0106] (6) The zeta potential of the nanofiltration membrane surface prepared in Example 3 and Comparative Example 1 was tested using Austrian Anton Paar surpass3 solid surface zeta potential tester.

[0107] The test process is as follows: 74.5ppm (0.001mMol / L) potassium chloride solution is used as the test solution; the nanofiltration membrane is cut into two 1*2cm rectangular pieces and fixed on the sample table of the instrument. The pH value of the solution is adjusted to 3, 4, 5, 6, and 9, and the Zeta potential of the nanofiltration membrane surface is tested based on the streaming potential and streaming current measurement methods. The test environment temperature condition is 25℃.

[0108] Fig.10 This is a comparison chart of the Zeta potential of the nanofiltration membranes prepared in Example 3 and Comparative Example 1. Fig.10 It shows that the nanofiltration membrane prepared in Example 3 has stronger electronegativity than the nanofiltration membrane provided in Comparative Example 1.

[0109] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0110] Although the above embodiments have been shown and described, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. Changes, modifications, substitutions and variations of the above embodiments by those of ordinary skill in the art are all within the scope of protection of the present invention.

Claims

1. A method for preparing a loose nanofiltration membrane, characterized in that: The following steps are involved: S1: mixing a nitrogen-containing precursor and an alkali and sintering the mixture to obtain carbon nitride, and then grinding the mixture to obtain exfoliated nanosheet carbon nitride; S2: dialyzing the exfoliated nanosheet carbon nitride in water to prepare a hydrophilic carbon nitride solution; S3: The ultrafiltration support bottom membrane is treated by infiltration with the hydrophilic carbon nitride solution; S4: placing the ultrafiltration support bottom membrane treated in step S3 into a solution containing an organic phase monomer to perform an interfacial polymerization reaction to obtain a loose nanofiltration membrane preform containing a polyamide separation layer; S5: heat-treating the loose nanofiltration membrane preform to obtain the loose nanofiltration membrane.

2. The preparation method according to claim 1, characterized in that: The nitrogen-containing precursor is selected from at least one of cyanamide, dicyandiamide, melamine, urea and thiourea; And / or, the alkali is selected from at least one of sodium hydroxide, potassium hydroxide and calcium hydroxide.

3. The preparation method according to claim 1 or 2, characterized in that: The nitrogen-containing precursor and the base are mixed in a mass ratio of (1.8-2.0):

1.

4. The preparation method according to claim 1, characterized in that: The sintering temperature is 300-350°C and the sintering time is 1-3h; Preferably, the sintering treatment is carried out in a muffle furnace, the temperature is raised to 300-350° C. at a heating rate of 4-6° C. / min, and the high-temperature sintering is carried out for 1-3 hours.

5. The preparation method according to claim 1, characterized in that: The concentration of carbon nitride in the hydrophilic carbon nitride solution is 1.0-3.0 mg / mL.

6. The preparation method according to claim 1 or 5, characterized in that: The dialysis treatment uses a 3500DA dialysis bag and the dialysis lasts for 12 to 48 hours.

7. The preparation method according to claim 1, characterized in that: The time of the infiltration treatment is 5 to 30 minutes.

8. The preparation method according to claim 1, characterized in that: The concentration of the organic phase monomer in the solution containing the organic phase monomer is 1 to 3 mg / mL; And / or, the organic phase monomer is selected from at least one of isophthaloyl chloride, terephthaloyl chloride, 1,3,5-trimesoyl chloride, pyromellitoyl chloride, cycloalkane polyacyl chloride, and polysulfonyl chloride; preferably, the organic phase monomer is 1,3,5-trimesoyl chloride; And / or, the reaction temperature of the interfacial polymerization reaction is 20-30° C., the reaction time is 2-10 min, and the reaction environment humidity is 45-70%.

9. A loose nanofiltration membrane, characterized in that: The method is prepared by any one of claims 1 to 8.

10. Use of the loose nanofiltration membrane according to claim 9 in the treatment of printing and dyeing wastewater.

Citation Information

Patent Citations

  • Carbon nitride compound and its preparation method and use

    CN106752122A

  • Zwitterionic functionalized carbon nitride nanosheet and positively charged nanofiltration membrane

    CN111517981A

  • Preparation method of nanofiltration membrane with low-pressure, high-flux and self-cleaning performance

    CN113413768A

  • Seawater desalination reverse osmosis membrane with both water flux and boron removal rate and preparation method of seawater desalination reverse osmosis membrane

    CN116440711A

  • Carbon nitrogen compound-polyamide laminated nanofiltration membrane as well as preparation method and application thereof

    CN117225187A